2009
DOI: 10.1016/j.specom.2009.01.004
|View full text |Cite
|
Sign up to set email alerts
|

PEAKS – A system for the automatic evaluation of voice and speech disorders

Abstract: We present a novel system for the automatic evaluation of speech and voice disorders. The system can be accessed via the internet platform-independently. The patient reads a text or names pictures. His or her speech is then analyzed by automatic speech recognition and prosodic analysis. For patients who had their larynx removed due to cancer and for children with cleft lip and palate we show that we can achieve significant correlations between the automatic analysis and the judgment of human experts in a leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(78 citation statements)
references
References 46 publications
2
70
0
6
Order By: Relevance
“…In almost all tasks, it was found that the automated scores correlated with the mean human judgments approximately as well as the judges' individual scores. Similar results were found with the system termed PEAKS [34] wherein speech recognition tools based on hidden Markov models (HMMs) were used to assess speech and voice disorders in subjects with conditions such as a removed larynx and cleft lip or palate. Therefore, automatic assessments of both speech and prosodic disorders are able to perform as well as human judges specifically when the system tends to include the requirements mentioned by [33].…”
Section: E E E P R O O F P R I N T V E R S I O Nsupporting
confidence: 62%
See 1 more Smart Citation
“…In almost all tasks, it was found that the automated scores correlated with the mean human judgments approximately as well as the judges' individual scores. Similar results were found with the system termed PEAKS [34] wherein speech recognition tools based on hidden Markov models (HMMs) were used to assess speech and voice disorders in subjects with conditions such as a removed larynx and cleft lip or palate. Therefore, automatic assessments of both speech and prosodic disorders are able to perform as well as human judges specifically when the system tends to include the requirements mentioned by [33].…”
Section: E E E P R O O F P R I N T V E R S I O Nsupporting
confidence: 62%
“…Some recent studies have proposed automatic systems to assess prosody production [33], speech disorders [34] or even early literacy [35] in children. Multiple challenges will be faced by such systems in characterizing the prosodic variability of LIC.…”
Section: E E E P R O O F P R I N T V E R S I O Nmentioning
confidence: 99%
“…The use of automatic speech processing techniques in order to allow an automatic speech intelligibility measurement has also been applied to articulation disorders diagnosed for patients with oral squamous cell carcinoma (Stelzle et al, 2011), speakers suffering from dysarthria (Vijayalakshmi et al, 2006;Hummel et al, 2011), or children with cleft lip and palate (CLP) (Maier et al, 2009). …”
Section: Speaker Pathologymentioning
confidence: 99%
“…speech for the same sentence to serve as a baseline, usually of good quality), and consequently of some time-frequency mapping between the tested and reference signals. Finally the approach in (Maier et al, 2009) proposed to predict subjective scores based on the word recognition rate (WRR) obtained by an Automatic Speech Recognition system. It was shown that WRR strongly correlates with the intelligibility of the voice.…”
Section: Introductionmentioning
confidence: 99%